Analysis of dengue specific memory B cells, neutralizing antibodies and binding antibodies in healthy adults from India. (July 2019) - Gunisetty, Sivaram; Nayak, Kaustuv; Chandra Rai, Ramesh; Chawla, Yadya; Reddy, Elluri Seetharami; Aggarwal, Charu; Maheshwari, Deepti; Panda, Harekrushna; Ansari, Nasim Akhtar; Singh, Prabhat; Kaur, Manpreet; Dixit, Kritika; et al.
Highlights: More than eighty percent adults immune to at least one dengue serotype. More than half of them are immune to all four dengue serotypes. Substantial interindividual variation observed in MBC, neutralizing/binding antibodies levels. Presence of the neutralizing antibodies correlate with presence of binding antibodies, but not vice versa. Levels of neutralizing and binding antibodies are not in perfect correlation. Abstract: Background: The Indian population is facing highest dengue burden worldwide supporting an urgent need for vaccines. For vaccine introduction, evaluation and interpretation it is important to gain a critical understanding of immune memory induced by natural exposure. However, immune memory to dengue remains poorly characterized in this region. Methods: We enumerated levels of dengue specific memory B cells (MBC), neutralizing (NT) and binding antibodies in healthy adults (n = 70) from New Delhi. Results: NT-antibodies, binding antibodies and MBC were detectable in 86%, 86.56% and 81.63% of the subjects respectively. Among the neutralizing positive subjects, 58%, 27%, 5% and 10% neutralized all four, any three, any two and any one dengue serotypes respectively. The presence of the neutralizing antibodies was associated with the presence of the MBC and binding antibodies. However, a massive interindividual variation was observed in the levels of the neutralizing antibodies (range, <1:50–1:30, 264), binding antibodies (range, 1:3, 000–1:134, 000, ) as well as the MBC (range = 0.006%–5.05%). Conclusion: These results indicate that a vast majority of the adults are immune to multiple dengue serotypes and show massive interindividual variation in neutralizing/binding antibodies and MBCs – emphasizing the importance of monitoring multiple parameters of immune memory in order to properly plan, evaluate and interpret dengue vaccines.